PRAKTIK PENERAPAN UNDANG-UNDANG HARMONISASI PERATURAN PERPAJAKAN UNTUK PAJAK PERTAMBAHAN NILAI DI PERUM PERHUTANI - Aisya Syafa (2023)
In order to optimize tax revenue in Indonesia, the government enacted Law Number 7 of 2021 or also known as the Law on the Harmonization of Tax Regulations (UU HPP). The Law on the Harmonization of Tax Regulations is a regulation that reforms taxation, particularly in the field of VAT. This study aims to formulate how the management of Perum Perhutani interprets accountability for the practice of implementing the Value Added Tax (VAT) Harmonization Tax Regulations Law. This research uses qualitative methods with an ethnomethodological approach. Through an analysis of indexicality, reflexivity, and contextual action, the results of this study are that Perum Perhutani has carried out a Self Assessment System and good accountability practices, according to Law Number 7 of 2021.